2014
DOI: 10.1002/jcb.24710
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of miR-144 in CsA Induced Proliferation and Invasion of Human Trophoblast Cells by Targeting Titin

Abstract: MicroRNAs (miRNAs) are endogenous 19-25 nucleotide noncoding single-stranded RNAs that regulate gene expression by blocking the translation or decreasing the stability of mRNAs. In this study, with the treatment of CsA (Cyclosporin A), we showed that miR144 expression levels were decreased while titin mRNA expression levels were increased in human trophoblast (HT) cells, and identified titin as a novel direct target of miR-144. Overexpression of miR-144 suppressed titin and its downstream signaling molecule su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…miRNAs function via base pairing with complementary sequences within mRNA molecules [20,21,22,23], cutting off the mRNA molecule on target genes, or inhibiting translation of target genes. Some research has indicated that miR-144 is downregulated in many cancers [24,25,26,27,28,29,30,31]. These previous findings coincide with our results, which identified that miR-144 is significantly downregulated in human lung cancer.…”
Section: Discussionsupporting
confidence: 92%
“…miRNAs function via base pairing with complementary sequences within mRNA molecules [20,21,22,23], cutting off the mRNA molecule on target genes, or inhibiting translation of target genes. Some research has indicated that miR-144 is downregulated in many cancers [24,25,26,27,28,29,30,31]. These previous findings coincide with our results, which identified that miR-144 is significantly downregulated in human lung cancer.…”
Section: Discussionsupporting
confidence: 92%
“…In our previous study, Cyclosporin A (CsA) has been revealed to inhibit miR‐144 expression to regulate proliferation and invasion of human trophoblast (HT) cells through miR‐144 targeting titin [Liang et al, ]. We demonstrated the mechanism by which CsA promotes titin expression to increase the vitality of HT cells.…”
mentioning
confidence: 80%
“…Recently, Opitz et al [] showed evidence of a previously unknown isoform of titin, termed as N2BA‐1, and this novel isoform is dominant in the fetus and almost absent by birth in the rat. In our previous study, we demonstrated that miR‐144 could inhibit HT cells’ proliferation and invasion via direct targeting titin [Liang et al, ]. Thus, it is likely that titin expression may be involved in the process of placentation and embryo development.…”
mentioning
confidence: 97%
“…Two microRNAs—miR-19 and miR-574 have been reported to be related to CsA immunosuppression effect. miR-19 has been reported to be downregulated by CsA in vitro[18] while miR-574 has been reported to be downregulated with acute rejection in human [19]. MiR-15 has been reported to be lower in urine with glomerulosclerosis.…”
Section: Introductionmentioning
confidence: 99%